Red blood cell metabolic responses to refrigerated storage, rejuvenation, and frozen storage. Issue 4 (10th March 2017) - D'Alessandro, Angelo; Gray, Alan D.; Szczepiorkowski, Zbigniew M.; Hansen, Kirk; Herschel, Louise H.; Dumont, Larry J.
Abstract : BACKGROUND: Storage of red blood cells (RBCs) under blood bank conditions promotes metabolic modulation within the RBC. This "metabolic storage lesion" may affect the quality and safety of the transfused RBCs. The aim of this study is to determine the metabolic changes in stored RBCs over 42 days of routine storage followed by a US Food and Drug Administration‐approved method of rejuvenation, freezing, and preparation for transfusion. STUDY DESIGN AND METHODS: We exploited a mass spectrometry‐based metabolomics approach to monitor 42‐day‐stored citrate phosphate dextrose/AS‐1 RBCs (n = 29) that were rejuvenated, glycerolized and frozen, then thawed and deglycerolized, and held for 24 hours at 1 to 6ºC in saline‐glucose. RESULTS: Previously reported metabolic alterations were confirmed in 42‐day‐old RBCs. In this study, in total, 181 (62%) of the biochemical compounds exhibited significant (p ≤ 0.05) change compared with Day 0 values. Rejuvenation restored adenosine triphosphate and 2, 3‐diphosphoglycerate levels, replenished purine reservoirs, up regulated glycolysis, increased levels of pentose phosphate pathway intermediates, and partially rescued glutathione biosynthesis. Increased levels of lysophospholipid in rejuvenated RBCs suggests the activation of recycling pathways of damaged membrane lipids, in which a total of 167 (57%) biochemical compounds showed significant change compared with Day 42 values. CONCLUSION: Rejuvenation reversed over one‐half of the metabolic biochemical compounds evaluated compared with Day 42 values, and the compounds were stable through frozen storage and preparation for transfusion. Rejuvenation promoted significant metabolic reprogramming, including the reactivation of energy‐generating and antioxidant pathways (the pentose phosphate pathway and glutathione homeostasis), salvage reactions, cofactor reservoirs, and membrane lipid recycling.